2016
DOI: 10.1590/1983-40632016v4639553
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical and sensorial quality of banana genotypes

Abstract: Despite the diversity of banana varieties in Brazil, only a few cultivars have the proper agronomic traits and fruit quality for commercial exploitation. This study aimed at evaluating the physicochemical traits and sensorial acceptance of banana genotypes, in order to identify those with potential for commercial growing. Six improved banana genotypes were assessed (BRS Maravilha, PC 0101, FHIA 18, TM 2803, YB 4203 and BRS Caipira), as well as three commercial cultivars (Grand Naine, Pacovan and Prata Anã). An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 14 publications
2
4
0
Order By: Relevance
“…Figure 1J overall organoleptic analysis revealed a wide diversity among SND ecotypes with most ecotypes having average general acceptability above 4, that is, 15 ecotypes and 4 ecotypes had less than 4 meaning that the largest percentage of ecotypes were more acceptable to the panelists. The results agrees with those reported by Reis et al (2016) who reported a linear correlation between the sensorial attributes and the overall acceptance of the bananas. Basing on this, it was observed that ecotypes K and A rated highest on almost all the attributes consistently and ecotype D scored the least on almost all the attributes and was the least liked.…”
Section: Organoleptic Analysis Of the Ecotypessupporting
confidence: 92%
“…Figure 1J overall organoleptic analysis revealed a wide diversity among SND ecotypes with most ecotypes having average general acceptability above 4, that is, 15 ecotypes and 4 ecotypes had less than 4 meaning that the largest percentage of ecotypes were more acceptable to the panelists. The results agrees with those reported by Reis et al (2016) who reported a linear correlation between the sensorial attributes and the overall acceptance of the bananas. Basing on this, it was observed that ecotypes K and A rated highest on almost all the attributes consistently and ecotype D scored the least on almost all the attributes and was the least liked.…”
Section: Organoleptic Analysis Of the Ecotypessupporting
confidence: 92%
“…According to Reis et al (2016), the external evaluation of fruits involves combinations of geometric and physical attributes, which directly influence the acceptability by consumers. The external dimensions of fruits presented significant differences among cultivars, and the 'Baianinha' cultivar presented the largest longitudinal diameter, followed by 'Pera IAC', 'Pera IAC 2000', 'Natal IAC' cultivars, which are equal to each other, and higher than 'Natal 112' cultivar, which in turn, was higher than 'Pera Rio' cultivar ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…In Brazil, the commercially exploited cultivars are Prata, Grand Naine, Williams, and Nanicão (Nomura, Cuquel, Damatto, Fuzitani, & Borges, 2017); however, they all have at least one undesirable characteristic for commercial crops, such as plant height, yield, harvest time, tolerance to pests and diseases, or low resistance to drought or cold (Nomura et al., 2013a). Regardless, the fruit quality is considered adequate for commercialization (Reis, Viana, Jesus, Santos, & Oliveira, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The Honduran Agricultural Research Foundation (FHIA) breeding program has developed several banana cultivars, such as FHIA 18 (AAAB), a Prata subgroup hybrid reputed among the banana type Prata (Reis et al., 2016). This cultivar has great potential for introduction into the Brazilian cropping system because the fruits of FHIA 18 have similar characteristics to the Prata, making this cultivar a viable substitute for the cultivar that is susceptible to the black Sigatoka fungus ( Mycosphaerella fijiensis , Morelet) and Panama disease ( Fusarium oxysporum f. sp.…”
Section: Introductionmentioning
confidence: 99%